2022
DOI: 10.3389/fendo.2022.1007980
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke and retinopathy during GLP-1 receptor agonist cardiovascular outcome trials: An eight RCTs meta-analysis

Abstract: PurposeTo explore the risk of stroke (including ischemic and hemorrhagic stroke) in type 2 diabetes mellitus treated with glucagon-like peptide 1 receptor agonist (GLP-1RA) medication according to data from the Cardiovascular Outcome Trials(CVOT).MethodsRandomized controlled trials (RCT) on GLP-1RA therapy and cardiovascular outcomes in type 2 diabetics published in full-text journal databases such as Medline (via PubMed), Embase, Clinical Trials.gov, and the Cochrane Library from establishment to May 1, 2022 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…A meta-analysis from 2022 by Wei et al has specifically evaluated the effect of GLP-1RA treatment on the outcome of stroke and reported a reduced risk ratio of 0.83 [0.73; 0.95] for total stroke after treatment with GLP-1RAs compared to placebo, which corresponds to an absolute risk reduction of 0.27% and a number needed to treat of roughly 370 persons for a period of 1.3 to 5.4 years based on the included clinical trials. 27 In conclusion, the results from our analyses substantiate the relevance of treatment with SGLT-2 inhibitors or GLP-1RAs in patients with T2D and concomitant high risk for cardiovascular disease, and furthermore, support the recommendation for SGLT-2 inhibitor treatment in patients with T2D and heart failure or established kidney disease. The lack of clinically relevant effects on mortality, cardiovascular and renal outcomes in the low-risk subgroup should be taken into consideration when deciding whether to use these compounds with higher costs in lowrisk T2D populations.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A meta-analysis from 2022 by Wei et al has specifically evaluated the effect of GLP-1RA treatment on the outcome of stroke and reported a reduced risk ratio of 0.83 [0.73; 0.95] for total stroke after treatment with GLP-1RAs compared to placebo, which corresponds to an absolute risk reduction of 0.27% and a number needed to treat of roughly 370 persons for a period of 1.3 to 5.4 years based on the included clinical trials. 27 In conclusion, the results from our analyses substantiate the relevance of treatment with SGLT-2 inhibitors or GLP-1RAs in patients with T2D and concomitant high risk for cardiovascular disease, and furthermore, support the recommendation for SGLT-2 inhibitor treatment in patients with T2D and heart failure or established kidney disease. The lack of clinically relevant effects on mortality, cardiovascular and renal outcomes in the low-risk subgroup should be taken into consideration when deciding whether to use these compounds with higher costs in lowrisk T2D populations.…”
Section: Discussionsupporting
confidence: 78%
“…This was mainly a result of the failure of SGLT‐2 inhibitors to reduce non‐fatal stroke compared to placebo (OR 1.01 (95% CI [0.89; 1.14])) despite that the SGLT‐2 inhibitors reduced other cardiovascular endpoints compared to placebo (MACE OR 0.87 [0.82; 0.93]) and showed no difference compared to GLP‐1RAs in our analysis (MACE OR 0.99 [0.91; 1.09]). A meta‐analysis from 2022 by Wei et al has specifically evaluated the effect of GLP‐1RA treatment on the outcome of stroke and reported a reduced risk ratio of 0.83 [0.73; 0.95] for total stroke after treatment with GLP‐1RAs compared to placebo, which corresponds to an absolute risk reduction of 0.27% and a number needed to treat of roughly 370 persons for a period of 1.3 to 5.4 years based on the included clinical trials 27 …”
Section: Discussionmentioning
confidence: 99%
“…50 However, three other studies reported no association between GLP-1 RA use and diabetic retinopathy. 44,45,49 A network meta-analysis assessing the comparative effectiveness of glucose-lowering drugs on the risk F I G U R E 3 Forest plot describing meta-analysis of DPP-4 inhibitor use and the risk of diabetic retinopathy among patients with type 2 diabetes, stratified by diabetic retinopathy incidence or progression. CI, confidence interval; DPP-4, dipeptidyl peptidase-4; HK; Hartung-Knapp.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first systematic review and meta‐analysis of observational studies evaluating the risk of diabetic retinopathy among users of incretin‐based drugs. There have been several previous systematic reviews evaluating this association, but these previous knowledge syntheses were restricted to randomized controlled trials 15,43–50 . Two systematic reviews assessed the risk of retinopathy with the use of DPP‐4 inhibitors but did not include a sufficient number of studies for meta‐analysis 15,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation